Application of Alum and Cassava Peel Starch (CPS) as Dual Coagulant in Surface Water - Yusof, Siti Nur Aishah; Othman, Norzila (Recent Trends in Civil Engineering and Built Environment, 2024)
In recent decades, surface water is increasingly threatened due to rapid development. The overdosing chemical coagulants in coagulation and flocculation has led to environmental problems and harmful to human health. Therefore, cassava peel starch (CPS) has been proposed as potential natural coagulant aid to remove turbidity, total suspended solids (TSS) and chemical oxygen demand (COD) concentration. According to the result in the present study, water quality of raw water collected from Parit Raja water treatment plant, Johor is classified as Class I to Class IIA. The mean values of temperature, turbidity, TSS and COD are 26.91 ˚C, 13.57 NTU (IIA), 8.89 mg/L (Class I) and 18.78 mg/L (Class I) respectively. Several batches of Jar tests have been conducted for optimization study of alum and cassava peel starch in context of pH value and coagulant dosage. In accordance to the findings, the optimal pH value for alum with CPS is pH 8 while the optimal coagulant dosage value for alum with CPS is 75:25 (11.25 mg/L of alum solution and 25 mg/L of CPS solution) was obtained as the percentages of removal of turbidity, TSS and COD values were higher than treatment using alum alone (92.41%, 8.75% and 94.68%). The result of the present study is reflected that CPS as natural coagulant is effective to facilitate the removals of turbidity, TSS and COD in surface water.